UGP gene expression and UDP-glucose pyrophosphorylase enzymatic activity in grafting annonaceous plants - Baron, Daniel [UNESP]; Bravo, Juliana P. [UNESP]; Maia, Ivan G. [UNESP]; Pina, Ana; Ferreira, Gisela [UNESP] (Springer Nature, 2016)
Grafting is commonly used to propagate commercial fruit species to ensure that the genetic characteristics of selected clones are maintained. However, the biochemical and molecular mechanisms involved in the graft incompatibility of woody trees are not well understood. We investigated the effect of grafting in vegetative growth, UDP-glucose pyrophosphorylase expression and activity of Annonaceous grafted plants: atemoya (Annona cherimola Mill. x Annona squamosa L.) ‘Thompson’ grafted onto different rootstocks, araticum-de-terra-fria (Annona emarginata Schltdl. H. Rainer “var. terra-fria”), araticum-mirim(Annona emarginata Schltdl. H. Rainer “var. mirim”) and biribá (Annona mucosa Schltdl. H. Rainer) at different post-grafting times. The growth of atemoya grafted onto araticum-mirim was lower than that of the rootstocks araticum-de terra-fria and biribá. The results also indicated that grafting alters UGPase gene expression; showing the combination atemoya grafted onto araticum-de-terra-fria (a compatible union) the higher levels of gene expression during the early stages of grafting development. However, no significant differences were detected in UGPase enzyme activity between the graft combinations. In addition, SDS-PAGE and MALDI-TOF analyses detected similar UGPase amino acid sequences in ungrafted atemoya samples to cherimoya (Annona cherimola Mill.), a female parent of the atemoya hybrid. These findings suggest that expression of the UGPase protein is related to graft compatibility in grafted Annona plants.
Keywords: Annonaceae; Enzymatic activity; Graft incompatibility; Plant propagation; UGP